Correlation of SARS-CoV-2 Viral Load and Clinical Evolution of Pediatric Patients in a General Hospital From Buenos Aires, Argentina - Brizuela, Martín Eduardo; Goñi, Sandra Elizabeth; Cardama, Georgina Alexandra; Zinni, María Alejandra; Castello, Alejandro Andres; Sommese, Leandro Matías; Farina, Hernán Gabriel (Frontiers in Pediatrics, 2022)
Background SARS-CoV-2 infection is associated with varying clinical severities. Pediatric cases represent less than 10% of total cases, with a mortality rate below 1%. Correlation of SARS-CoV-2 viral load in respiratory samples and severity of disease in pediatric patients is scarce. The cycle threshold (CT) value for the detection of SARS-CoV-2 is an indirect indicator of viral load in analyzed respiratory samples. Objective The aim of this study was to describe CT values and their correlation with clinical manifestations, epidemiology and laboratory parameters in pediatric patients with confirmed COVID-19. Methods In this observational, retrospective, analytic and single-center study we include patients under 15 years with confirmed COVID-19 by RT-PCR SARS-CoV-2 admitted to the Isidoro Iriarte Hospital (Argentina) between 1st March 2020 and 30th April 2021. Results 485 patients were included, the distribution according to disease severity was: 84% (408 patients) presented mild disease, 12% (59 patients) moderate disease and 4% (18 patients) severe disease. Patients with moderate and severe illness presented increased hospitalization rates, prolonged hospitalization, higher frequency of comorbidities and oxygen and antibiotics requirement. Viral load was associated with severity of clinical manifestations and age under 12 months. No patient required admission to PICU nor mechanical ventilation. No deaths were registered. Conclusions In this study, the viral load of SARS-CoV-2 in respiratory samples, determined by the cycle threshold, was significantly correlated with moderate to severe cases and with age.